The policing of illicit drugs on local trains in the Gauteng south and Northwest regions: research - Mabudusha, S. A. (Acta criminologica, 2018)
Rail transport is generally regarded as one of the safest modes of transport, particularly when compared to road transport, since it experiences fewer accidents and fatalities. However, annual reports by the South African Rapid Rail Police Unit show the security of commuters within the rail transportation environment in a different light. This article presents the challenges faced by the South African police deployed in the rail environment in reducing the use of illicit drugs on local trains. Using purposive sampling techniques, face-to-face interviews were conducted with the Rapid Rail Police Unit of the South African Police Service (SAPS) and the Passenger Rail Agency of South Africa’s (PRASA) Protection Security Service to obtain in-depth first-hand information on illicit drug use on trains. The study found that the demand-supply business of the illicit use of drugs, such as marijuana, is commonplace and an everyday occurrence on local trains. Issues such as overcrowding on local trains and a shortage of police personnel are the main challenges faced by the police on local trains. This study recommends an increase in police visibility on trains, the use of drug detection dogs on train platforms and enhanced communication between the police and stakeholders such as the PRASA Protection Security Service (PSS) and commuter forums.